Strategy To Increase Individual Tax Payer Compliance - Alfian Saputra; Nurwanah Nurwanah; Amiruddin Amiruddin; Yana Ameliana (SIMAK, 2023)
This research aims to evaluate the influence of awareness, socialization, tax services and tax sanctions on the level of compliance of individual taxpayers at the South Makassar Pratama Tax Service Office. This research adopts a descriptive quantitative approach using primary data. The research sample consisted of 100 individual taxpayers registered at the South Makassar Primary Tax Service Office. The sampling method was carried out using a purposive sampling technique, where respondents were selected based on certain criteria that were relevant to the research objectives. The data collection method is carried out through surveys by distributing questionnaires to selected respondents. Hypothesis analysis in this research uses multiple linear regression techniques with the help of SPSS version 25 statistical software. The results of the research show that tax awareness, tax socialization, tax authorities services, and tax sanctions positively and significantly influence the level of individual taxpayer compliance at KPP Pratama Makassar South. This research contributes to further understanding of the factors that influence tax compliance at the individual level. The implications of these findings can help formulate more effective policies and strategies in increasing the level of tax compliance, especially in the personal tax environment in the region.